2006
DOI: 10.1243/09544100jaero84
|View full text |Cite
|
Sign up to set email alerts
|

Plume impingement investigation using Monte-Carlo computations

Abstract: Numerical simulations have been performed to explore the effects of important design parameters on impingement disturbance properties of multiple hydrazine thruster plumes. The particle behaviour of the far-field plume flows near the impingement surfaces is modelled using the collisionless molecular direct simulation Monte-Carlo method with the inflow boundary condition derived from the velocity and temperature profiles at the nozzle exit. The entering molecular motions and the impact interactions between mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…42 The main benefit of the DSMC is its numerical stability, and it does not depend on similarity parameters like the Mach number, Reynolds number,, 43 furthermore, with the development of supercomputers, 44 DSMC technique in the latest years, has become a diverse and successful one. 45 Though DSMC is the right approach for modeling microscale flows, 4648 at low speeds, the statistical noise is significant and limits the accuracy of results. Also, it has drawbacks such as slow convergence and requirement of a large number of simulated molecules; a thorough description is given in literature.…”
Section: Methodsmentioning
confidence: 99%
“…42 The main benefit of the DSMC is its numerical stability, and it does not depend on similarity parameters like the Mach number, Reynolds number,, 43 furthermore, with the development of supercomputers, 44 DSMC technique in the latest years, has become a diverse and successful one. 45 Though DSMC is the right approach for modeling microscale flows, 4648 at low speeds, the statistical noise is significant and limits the accuracy of results. Also, it has drawbacks such as slow convergence and requirement of a large number of simulated molecules; a thorough description is given in literature.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] Chung et al 3) used the N-S method to compute the flow in the subsonic region of a low density nozzle and the DSMC code was taken for its supersonic portion, respectively. Ó 2009 The Japan Society for Aeronautical and Space Sciences Vashchenkov et al 4) studied the plume backflow phenomenon for various shapes of a supersonic nozzle with a low Reynolds number and concluded that use of the combined N-S/DSMC approach is essentially important to simulate flow in a rarefied environment.…”
Section: Introductionmentioning
confidence: 99%
“…Ó 2009 The Japan Society for Aeronautical and Space Sciences Vashchenkov et al 4) studied the plume backflow phenomenon for various shapes of a supersonic nozzle with a low Reynolds number and concluded that use of the combined N-S/DSMC approach is essentially important to simulate flow in a rarefied environment. In addition, Yang 5) investigated the effect of thruster plume impingement on the satellite using the collisionless DSMC method for simplicity in conjunction with N-S method. Here, the internal flow in a nozzle is assumed to be laminar, and the turbulence effect is ignored.…”
Section: Introductionmentioning
confidence: 99%